Alterações morfológicas foliares em cultivares de canade- açúcar em resposta à deficiência hídrica - Pincelli, Renata Passos [UNESP]; Silva, Marcelo de Almeida [UNESP] (My University, 2012)
The aim of this study was to determine the response of morphological traits of four tolerant and susceptible sugarcane cultivars (SP81-3250, SP83-2847, RB855453 and RB72454) related to two water regimes. At 84 days after emergence the plants were submitted to water availability treatments (no water deficiency and water deficiency), and evaluated in three periods: zero, 28 and 56 days, after implantation of these treatments (DAT). The cultivars SP81- 3250 and SP83-2847, when subjected to water stress for prolonged periods in early development, present higher leaf width, less damage to the green leaf number and leaf area, an increase in stomatal density in adaxial and abaxial leaf surface, and higher production of dry matter, and therefore were considered tolerant. The leaf +3 length not allowed to characterize the varieties to drought tolerance.
Leaf morphological changes in sugarcane cultivars in response to water deficit
Keywords: Leaf área; Saccharum spp; Stomatal density; Varieties; Water availability